2014
DOI: 10.3390/ijms151017778
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Combined Grape Pomace and Omija Fruit Extracts on Hyperglycemia, Adiposity and Hepatic Steatosis in db/db Mice: A Comparison with Major Index Compounds

Abstract: This study investigated the effects of combined grape pomace and omija fruit extracts (GO) on diabetes-related metabolic changes in type 2 diabetic db/db mice. The effects of GO were compared with those of a resveratrol and schizandrin mixture (RS), which is a mixture of major components of GO. Mice were fed a normal diet with RS (0.005% resveratrol and 0.02% schizandrin in diet, w/w) or GO (0.3% grape pomace ethanol extract and 0.05% omija fruit ethanol extract in diet, w/w) for seven weeks. RS and GO not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…It is supposed that some flavonoids and polyphenols in GPE+OFE may have synergistic effects via their interaction, although we did not determine it in the present study. This hypothesis is supported by a previous our study in which the effects of GPE+OFE were compared with those of resveratrol and schizandrin mixture (RS), which is a mixture of the major index components of GPE+OFE [ 47 ]. GPE+OFE have more protective effect on hyperglycemia, adiposity and hepatic steatosis in type 2 diabetic mice than RS [ 47 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is supposed that some flavonoids and polyphenols in GPE+OFE may have synergistic effects via their interaction, although we did not determine it in the present study. This hypothesis is supported by a previous our study in which the effects of GPE+OFE were compared with those of resveratrol and schizandrin mixture (RS), which is a mixture of the major index components of GPE+OFE [ 47 ]. GPE+OFE have more protective effect on hyperglycemia, adiposity and hepatic steatosis in type 2 diabetic mice than RS [ 47 ].…”
Section: Discussionsupporting
confidence: 55%
“…This hypothesis is supported by a previous our study in which the effects of GPE+OFE were compared with those of resveratrol and schizandrin mixture (RS), which is a mixture of the major index components of GPE+OFE [ 47 ]. GPE+OFE have more protective effect on hyperglycemia, adiposity and hepatic steatosis in type 2 diabetic mice than RS [ 47 ]. Another possibility is that other unknown active components present in extracts of GPE+OFE also play important in their biological effects.…”
Section: Discussionsupporting
confidence: 55%
“…Phytochemicals are known to possess antioxidant properties with effective anti-inflammatory, antiallergic, hepatoprotective, antithrombotic, antiviral, and anticarcinogenic activities ( 7 9 ). Among them, polyphenols such as resveratrol, catechins, and anthocyanins are of great interest due to their wide distribution in plants and potent health-promoting activities ( 10 12 ). Treatments with phytochemicals obtained from various sources have been demonstrated to regulate the levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) in HFD-fed rats ( 13 15 ).…”
mentioning
confidence: 99%
“…GP alone exerted a significant anti-postprandial hyperglycemic effect in diabetic mice [22], while GPOF lowered fasting hyperglycemia in type 2 diabetic db/db [13]. It is important to identify that GPOF can prevent blood glucose rise in DIO condition in the early stage (12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Omija (Schisandrachinensis), another polyphenol-rich plant that has been used in traditional Chinese medicine and pharmacotherapy of European and other countries, plays an important role in lowering blood glucose level and regulating the endocrine and immune systems and antioxidant enzyme activities [10,11]. We previously demonstrated that combined extracts of grape pomace (GP) and GP plus omija fruit (GPOF) showed anti-obesity and anti-inflammatory effects in diet-induced obese (DIO) mice [12] and an anti-diabetes effect in db/db mice [13]. The aims of the present study were to examine whether GPOF has blood glucose-and oxidative stress-lowering effects in mice fed an obesogenic diet and compare its effects with those of GP.…”
Section: Introductionmentioning
confidence: 99%